Strategi Promosi Dengan Model K-pop Untuk Meningkatkan Penjualan Pada E-commerce Tokopedia - Gilang Aryogy Surya Prayoga; Poppy Febriana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The more advanced the era of technology is also increasingly sophisticated and old habits are abandoned and switch to new habits. One of them is shopping habits, since the introduction of the internet and android, buying and selling activities are easier with the existence of e-commerce. E-commerce is a type of business that allows companies or individuals to buy or sell goods via the internet (online). And one of them is Tokopedia. In recent years, many e-commerce companies often use Korean artists because young people's interest in the influence of Korean culture is very strong. Therefore, researchers want to try to explain why they use brand ambassadors from Korea and how they succeed in carrying out these marketing strategies. This research uses marketing communication theory and marketing mix theory. These theories help researchers to conclude a marketing strategy phenomenon by using Korean artists as brand ambassadors. The method used is qualitative with a phenomenological approach. Researchers approach the data with observation and in-depth interviews to find out a phenomenon of human interest in following a cultural current. data analysis using SOSTAC theory, namely Situation analysis, Objectivities, Strategy, Tactics, Action and Control. The conclusion obtained by the researcher is that the use of e-commerce marketing with Korean artist brand ambassadors can attract consumers, especially young people.